Simulation of "a week care unit" organization in an academic hospital. (May 2015) - Sinnaeve, G; Beguin, C; Chevalier, P; Philippe, M
Abstract: Poor bed allocation to each specialty might lead to a surplus of available beds during weekends. The introduction of a "week unit" that is only available during working days may improve the efficiency of bed allocation by uniting the patient flow of two regular units, before converting the regular beds of one unit into week beds. In order to test the possible introduction of this system in three services of the Saint-Luc hospital, we created a simulation model that considers new allocation rules to direct the patients into the right unit.